Evaluating two nanosilica dimensional range for the consolidation of degraded silicate stones. (25th April 2022) - Stucchi, Neva Maria Elisabetta; Tesser, Elena; Zaccariello, Gloria; Antonelli, Fabrizio; Benedetti, Alvise
Graphical abstract: Highlights: Silica nanoparticles of 50 and 120 nm have been synthetized by Stöber method and dispersed at 5% in an ethanol:water solution. The chemical compatibility between silica nanoparticles and silicate stones was guaranteed. No significant colour and morphological alterations appeared on treated surfaces after the application of the strengthening agent. A certain reduction of water absorbed was demonstrated. Aggregation tendency of SNP when in contact with water was observed. The formation of SNP clusters developed structures with dimensions higher than those of porous diameters impeding sometimes the penetration of the treatment. Abstract: The application of silica nanoparticles strengthening agents in conservation of monumental and architectural heritage field is currently a challenge of particular interest. Some commercial products are already on the market and several studies highlighted the related strength and weakness. In order to contribute to the knowledge of the interaction between nanoparticles and stone materials as well as to provide key elements to improve the approach to conservative treatments, two silica nanoparticles products for the consolidation of silicate stones were developed in the laboratory. Bianco Sardo granite, Firenzuola and Muggia sandstones were selected as substrates for the experimentation after a laboratory investigation of their open porosity. Silica nanoparticles having two different particles size, both compatible with the porosimetric features of the selected stones, were synthesized and dispersed in an ethanol–water solution. The carrier was specifically studied for avoiding the agglomeration of silica nanoparticles and facilitating the penetration of the products in the stone substrates. Sound and artificially aged specimens were impregnated by capillary absorption method and the effectiveness of the treatment was evaluated through morphological and physical analyses. Microscopic observations, colorimetric analyses, sponge tests, ultrasound velocity determinations and porosimetric measurements showed positive results, which encourage, on one hand, the use of silica nanoparticles for consolidating silicate stones, on the other hand, further researches aimed to improve the synthesized products by reaching a deeper penetration and the reduction of water absorption.